SUN5 forms a regular protein lattice reinforcing the sperm head–tail junction - Jonas Moecking; Svetlana Doroshev; Miguel Ricardo Leung; Tzviya Zeev-Ben-Mordehai (Proceedings of the National Academy of Sciences, 2026)
Spermatozoa strongly rely on their streamlined morphology to successfully fertilize an oocyte. A striking example of a morphological defect resulting in infertility is acephalic spermatozoa syndrome, a rare but severe condition leading to detachment of the sperm head and tail. Among the most common genetic causes for this syndrome are mutations in the linker of nucleo- and cytoskeleton (LINC) complex component SUN5. LINC complexes typically reside in the nuclear envelope, the double-membrane surrounding the nucleus, where they establish a physical bridge between nucleus and cytoplasm. This localization allows them to transduce mechanical signals from the cytoplasm to the nucleus and to regulate nuclear morphology. In sperm, LINC complexes are essential for a multitude of morphological changes during sperm development, including the reshaping of the nucleus and establishing a stable head–tail junction. Here, using superresolution fluorescence microscopy, we find that sperm-specific SUN5 localizes to the base of the head in human, mouse, and boar sperm. By applying in situ cryoelectron tomography, we find an extensive hexagonal lattice in the nuclear envelope in this region. This lattice appears to maintain a consistent close apposition between the inner and outer nuclear membranes (ONM). Further structural analysis supports a model in which LINC complexes form this lattice by laterally interacting at the ONM. Overall, this study sheds light on nuclear envelope organization in the highly streamlined sperm cell, providing a structural basis for uniform nuclear envelope spacing maintained by a LINC lattice and rationalizing the disruptive effects of SUN5 mutations.